High frequency stimulation of the STN restored the abnormal high-voltage spindles in the cortex and the globus pallidus of 6-OHDA lesioned rats. (19th May 2015) - Yang, Chen; Zhang, Jia-Rui; Chen, Lei; Ge, Shun-Nan; Wang, Jue-Lei; Yan, Zhi-Qiang; Jia, Dong; Zhu, Jun-Ling; Gao, Guo-Dong
Highlights: Dopamine depletion increased HVSs activity in the M1 cortex and the GP. STN plays a role in HVSs modulation both in M1 cortex and GP. STN high, but not low, frequency stimulation restored the abnormal HVSs. Abstract: Many studies showed that abnormal oscillations in the cortical-basal ganglia loop is involved in the pathophysiology of Parkinson's disease (PD). In contrast to the well-studied beta synchronization, high-voltage spindles (HVSs), another type of abnormal oscillation observed in PD, are neglected. To explore the role of subthalamic nucleus-deep brain stimulation (STN-DBS) in HVSs regulation, we simultaneously recorded the local field potential (LFP) in the globus pallidus (GP) and electrocorticogram (ECoG) in the primary motor cortex(M1) in freely moving 6-hydroxydopamine (6-OHDA) lesioned or control rats before, during, and after STN-DBS. Consistent with our previous study, HVSs occurrence, duration, and relative power and coherence between the M1 cortex and GP increased in 6-OHDA lesioned rats. We found that high but not low frequency stimulation restored the abnormal HVSs activity and motor deficit. These results suggest that the STN is involved in the abnormal oscillation between the M1 cortex and GP.